Gender, remmitances [i.e. remittances] and development the case of Filipino migration to Italy. - Ribas, Natalia; Garcia Dominguez, Mar.; International Research and Training Institute for the Advancement of Women (Santo Domingo, Dominican Republic United Nations International Research and Training Institute for the Advancement of Women, 2008)
For this study, UN-INSTRAW has partnered with the International Fund for Agricultural Development (IFAD) in order to examine the impact and potential of remittances for making positive contributions to sustainable and gender-sensitive local development in the rural Philippines. One of the particular features of this investigation was the active participation of an association of Filipina migrant women in Rome, Italy, the Filipino Women's Council (FWC) in the research process. After the first section with the theoretical framework that guided the research process, followed by a brief overview of the study's main objectives and the methodology used in the collection and analysis of the data, part two characterizes the migratory and remittance flows between the Philippines and Italy, and provides an overview of some of the key actors currently working on initiatives linked to migration, remittances and development. This is followed by an analysis of remittances' impact and potential for promoting gender- sensitive sustainable rural development and food security in the communities of origin studied. The fourth section of this paper highlights some of the conclusions reached during a validation workshop in which Filipino migrants in Rome met with the project researchers to discuss this study's results and explore possible initiatives for future action. Finally, the conclusions of this study are presented along with a series of recommendations for future policy and research in this area--Publisher's description.
Introduction -- Filipino migratory and remittances flows -- Impacts of remittances on rural development and household food security -- Recommendations.
Cover title.
"Lead researcher, Natalia Ribas ; report prepared by Victoria Simmons and Mar Garcia"--P. [2].
Also available online.
UCWS-2014-G-1854 donated by S. Panopio UN-INSTRAW 8-27-09
Keywords: Emigrant remittances -- Philippines; Sex role -- Philippines; Women foreign workers -- Italy; Foreign workers, Philippine -- Italy; Filipinos -- Employment -- Italy; Philippines -- Emigration and immigration -- Economic aspects; Italy -- Emigration and immigration -- Economic aspects